Examining the Elasticity of New Zealand's Current Account to the Real Exchange Rate - Kam Szeto; David Oxley (New Zealand Government, The Treasury, 2014)
The main purpose of this paper is to supplement the existing literature by quantifying the elasticity of New Zealand's current account to changes in the real exchange rate. The unusual composition of New Zealand's current account balance – particularly the large income deficit and the importance of the agricultural sector to the goods balance – suggests that this relationship for New Zealand may differ from that for other developed countries. As a result, we focus on modelling the relationship between New Zealand's exchange rate and the current account stripped of four main components: the net investment income balance, dairy exports, the value of both oil exports and imports, and education services exports: what we call the `adjusted' balance. We find that the responsiveness of New Zealand's current account to the real exchange rate is towards the lower end of most estimates used in other studies. Given that the trade elasticity is a key variable in macro-balance models of exchange rate valuation, we conclude that some previous studies may have underestimated the magnitude of the real exchange rate adjustment needed to help achieve external equilibrium in the long run.
Keywords: F32; F41; 330; Current account elasticity; exchange rate; Leistungsbilanz; Elastizität; Kaufkraftparität; Außenwirtschaftliches Gleichgewicht; Schätzung; Neuseeland